Parenting Styles and the Development of Socio-Emotional Regulation Skills in Preschool Children - Rahmatallahi Taiye Ojibara (Journal of Psychometric Research)
The study employed descriptive survey design to investigate the Parenting Styles and the Development of Socio-Emotional Regulation Skills of Preschool Children. Two hundred (200) Preschool respondents were randomly selected from ten (10) pre-primary schools; five (5) public and five (5) private schools. Parenting Styles Questionnaire (PSQ) and a self-Constructed Rating Scale for preschool Children's Socio-Emotional Rating Scale (PCSRS) were used to elicit information about the preschool parents' parenting styles and the rate scale for evaluation about their Socio-Emotional Skills displayed in the classroom. Validity and reliability studies of the measurement tools have been conducted. The data collected were analysed using statistical software SPSS 20.0 (Statistical Software Package for Social sciences). The findings revealed that that the dominant parenting Styles is authoritative parenting styles and the index of Socio-Emotional Regulation Skills are in the following order; friendship Skill, cooperation skill, responsibility skill, communication skill and the last is the empathy skill.